AN UNDESCRIBED SPECIES OF CALOTHYRIOPSIS ON APPLE - A.W. SUBHEDAR; V.G. RAO (REINWARDTIA, 1980)
The new species Calothyriopsis mali Subhedar & V.G. Rao (Fam.: Microthyriaceae), collected for the first time on apple fruits from India, is described and illustrated.